RELATIONSHIP BETWEEN ATRIAL FIBRILLATION, RHO KINASE ACTIVITY AND CONNEXIN40. STUDY IN END-STAGE RENAL DISEASE PATIENTS ON HAEMODIALYSIS. (April 2021) - Calò, Lorenzo; Bertoldi, Giovanni; Pagnin, Elisa; Rossi, Barbara; Fragasso, Antonio; Gobbi, Laura; Rigato, Matteo
Abstract : Objective: Evidence on cellular/molecular mechanisms leading to atrial fibrillation (AF) are scanty. Recently, it has been proposed a role for Rho Kinase (ROCK) pathway in terms of increased expression of ROCK, and myosin-phosphatase-target-subunit-1 (MYPT-1), downstream target of ROCK pathway, which correlated with the increased expression of Connexin40 (Cx40), an integral membrane protein of heart gap junctions, fundamental for the rapid cell-cell transfer of action potential. AF is the most frequent arrhythmia in CKD and dialysis patients in which we observed increased MYPT-1 phosphorylation which correlated with their LV mass. Given the ROCK established role in cardiovascular-renal remodelling, induction of impairment of cell-to-cell coupling/potential conduction leading to AF, we evaluated in dialysis patients with AF, the phosphorylation state of MYPT-1, expression of Cx40 and their relationship to support their involvement in AF. Design and method: 11 AF-dialysis patients (DPAF) under chronic bicarbonate dialysis 3-times/week (8 males, 3 females, 49–91yo), 11 sinus rhythm-dialysis patients (DP) (7 males, 4 females, 53–91yo) and 11 healthy subjects (C) (7 males, 4 females, 26–38yo) were enrolled. Mononuclear cells MYPT-1 phosphorylation state, Cx40 expression and ROCK inhibitor fasudil's effect were determined by Western blot. LV mass and left atrial systolic volume were measured by M-mode echocardiography. Results: DPAF's phospho-MYPT-1 was increased vs DP and C (1.57 ± 0.17 du vs 0.69 ± 0.04 vs 0.51 ± 0.05, p < 0.0001). MYPT-1 phosphorylation in DP was also higher vs C, p = 0.009. Cx40 was higher in DPAF (1.23 ± 0.12 vs 0.74 ± 0.03 vs 0.69 ± 0.03, p < 0.0001). DPAF's phospho-MYPT-1 correlated with Cx40 (r = 0.84, p = 0.0014), with cardiac left atrial systolic volume (r = 0.72, p = 0.013) and with LV mass (p = 0.014). Cardiac left atrial systolic volume was increased in DPAF compared with DP (44.45 ± 1, 38 vs 35.09 ± 2, 62, p = 0.005) and also significantly correlated with LV mass (r = 0.60, p = 0.049). In DPAF Fasudil reduced MYPT-1 phosphorylation (p < 0.01) and Cx40 expression (p = 0.03). Conclusions: These data confirm at mechanistic level a significant role of ROCK pathway, MYPT-1 and Cx40 in the mechanisms leading to AF in dialysis patients. The clarification on a mechanistic basis of this relationship/association should contribute to provide mechanistic explanations for AF generation and identify potential pharmacological targets for translations into treatment to AF.